Evaluation of fire, high-temperature and water erosion resistance of fiber-reinforced lightweight pozzolana-based geopolymer mortars - Silva G. (2019)
The development of new building materials requires intensive analyses of their durability under aggressive conditions. Therefore, the current study evaluated the capacity of a fiber-reinforced lightweight pozzolana-based geopolymer mortar to resist the action of fire, high temperatures and water erosion. The fire resistance and heat absorption capacity were evaluated through the exposure of disc samples to a direct flame at 1000 °C and the measurement of reverse-side temperature, respectively. To evaluate the high-temperature resistance, uniaxial compression tests were performed on cubic samples after their exposure to oven-temperatures of 300°C, 500°C, 800°C, and 1000°C. Finally, water jet erosion and permeability tests were performed to analyze the interaction of the material with water. The results of the fire tests indicate that fiber-reinforced lightweight pozzolana-based geopolymer mortars are able to absorb up to approximately 65% of heat flame with only slight degradation. On the other hand, uniaxial compression tests showed a temperature resistance up to 800°C, above this temperature the cubic samples experimented significant volumetric changes that might have been caused by a reaction of remaining hydrogen peroxide or gas expansion. Finally, water exposure tests showed that the material is highly permeable and has a remarkable resistance to water erosion. © Published under licence by IOP Publishing Ltd.